ROFA' ALIF SIGN AS A SYMBOL OF POLICY AND FIRMNESS IN LEADERSHIP - Nailah Kaltsum; Leoni Wilyam (Yayasan Haiah Nusratul Islam, 2025)
The rofa' alif sign in Arabic grammar not only has a grammatical function, but also contains symbolic meaning that is relevant to leadership values. This research aims to analyze the correlation between the symbolism of Rofa' Alif and the principles of policy and firmness in Islamic leadership. The method used is a descriptive qualitative study with a semiotic approach, including analysis of the text of the Nahwu book, interpretation, as well as interviews with Arabic language experts and Islamic leadership figures. The research results show that the rofa' alif sign represents firmness of principles, which is reflected in the straight and upright form of the alif, as well as justice because its use is limited to certain grammatical structures. Apart from that, this symbol also depicts wisdom through contextual flexibility in its application. These findings indicate that rofa' alif can be used as a symbol to frame an ideal leadership model that integrates firmness and wisdom, in accordance with leadership values in Islam. This research contributes to a new understanding of the relationship between Arabic linguistics and leadership concepts, and offers a unique perspective for the development of cultural and linguistic values-based leadership theories.